Pyridinium-clubbed dicationic ionic liquid electrolytes for efficient next-generation photo harvesting. (9th April 2018) - Dhar, Abhishek; Kumar, Nadavala Siva; Asif, Mohammad; Vekariya, Rohit L.
Abstract : A new series of pyridinium based dicationic ionic liquids was designed and synthesized. The synthesized ionic liquids have excellent thermal stability and good ionic conductivity. They can be used as electrolytes in photovoltaic devices. Abstract : We have developed a new series of pyridinium based dicationic ionic liquids (DCILs) having excellent thermal stability and good ionic conductivity. The effectiveness of these DCIL based electrolytes in photovoltaic devices and the effect of different anions ( e.g. iodine, bromide, and thiocyanate) versus the device performance are studied by cyclic voltammetry (CV), current–voltage ( I – V ) characteristics and electrochemical impedance spectroscopy (EIS). The electrolyte 2PrSCN based device C exhibited the highest photo conversion efficiency (PCE) of 5.23% under 1 sun (100 mW cm −2 ) illumination of light. We have also analyzed the influence of various anions in metal-free dye-sensitized TiO2 and the DCIL interface using the EIS technique. Device C based on 2PrSCN shows excellent long-term stability, maintaining <95% of the initial efficiency after 500 h.